2019
DOI: 10.4103/ijmr.ijmr_36_18
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology & therapeutic options of carbapenem-resistant Gram-negative bacteria

Abstract: Background & objectives: The growing incidence and the wide diversity of carbapenemase-producing bacterial strains is a major concern as only a few antimicrobial agents are active on carbapenem-resistant bacteria. This study was designed to study molecular epidemiology of carbapenem-resistant Gram-negative bacterial (GNB) isolates from the community and hospital settings. Methods: In this study, non-duplicate GNB were isolated from clinical specimens, and phenotypic tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
17
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 15 publications
6
17
3
Order By: Relevance
“…Previous studies found the efflux pump by the molecular technique such as PCR and observed that AcrAB efflux pump and mdtK efflux pump existed in CRE isolates. 23,41 In the current study, carbapenemase enzymes were detected by Carba NP test and MHT in 98% and 95%, respectively, which was in line with another study carried by Elawady et al 44 and Garg et al 45 who reported good sensitivity and specificity of Carba NP test.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies found the efflux pump by the molecular technique such as PCR and observed that AcrAB efflux pump and mdtK efflux pump existed in CRE isolates. 23,41 In the current study, carbapenemase enzymes were detected by Carba NP test and MHT in 98% and 95%, respectively, which was in line with another study carried by Elawady et al 44 and Garg et al 45 who reported good sensitivity and specificity of Carba NP test.…”
Section: Discussionsupporting
confidence: 92%
“…The unusually high prevalence of bla VIM (50% of bla NDM positive isolates) was also reported previously from our centre (Rahman et al, 2018). Another study from North India reported bla VIM in 18.4% (52/ 282) of carbapenem resistant isolates (Garg et al, 2019). Aminoglycosides in combination with other antibiotics such as tigecycline are often used for treating infections caused by carbapenem and colistin resistant K. pneumoniae (Petrosillo et al, 2019).…”
Section: Discussionsupporting
confidence: 81%
“…In a cross-sectional, multicenter survey from Dubai, all the studied P. aeruginosa isolates were colistin sensitive [ 194 ]. On the other hand, the rate of resistance was 22% in a report from India [ 195 ], and 15% in a nationwide Italian survey [ 196 ]. Ongoing surveillance is needed on a global scale, to observe and mitigate the spread of polymyxin resistance in this hostile pathogen.…”
Section: Special Features and Spread Of Polymyxin Resistance Amongmentioning
confidence: 99%